Plano de carreira do magistério de Suzano: análise do processo de elaboração e implementação da lei complementar nº 190/2010 e da lei municipal nº 4.392/2010 - Souza, Ingrid Costa Ribeiro [UNIFESP] (2019)
This research's theme is the process of elaboration and implementation of the statute and mastership career path in Suzano. The choice of this object of study is justified by the fact that studies about teaching career conducted by the Teacher Remuneration Observatory Survey (TROS) to have focused their work on studies about Statutes and Career Plan of States and Capitals, however did not concentrate in the cases of municipalities and in the construction of public policies to Teaching Career in these locations. Aiming as a study object the process of elaboration and implementation of the statute and mastership career path in Suzano, the question that guided this research has been to know in which extent teachers participation influenced the elaboration of this bill and corroborated the guarantee of policies for the appreciation of teachers in the county. The main goal was to analyze the construction process of Suzano's mastership career path, regarding the existent conflicts among the government, the union, and the teacher's participation in Complementary Law 190/2010 and the Municipal Law nº4.392/2010, as well as the changing in the law after its approval by the municipal legislature. The methodology used was the case study emphasizing documentary research on municipal law, especially, Suzano's Mastership Carrer Path, the national law on the career path, as well as international documents and bibliographic research about the academic production on unionism and teacher's work conditions. To comprehend teachers' participation in this process, semi-structured interviews were made with a municipal union's member, three Municipal Education Secretariat representatives, three teachers that took part in a strike in the period, two teachers that participated in the workgroup and the county’s mayor during the elaboration and approval period of the statute and the career path. The interviews content was categorized and analyzed according to Laurence Bardin’s Method. The Dialectical and historical materialism, whose elements corroborated the comprehension of Suzano’s mastership career path in historical terms as well as its controversies, was embraced as an analysis method. The theoretical framework embraced to discuss the career path was Rubens Camargo, Márcia Jacomini e João Monlevade. As a conclusion is possible to highlight, although the formation of a workgroup with the task of elaborating the statute and the career path for the Suzano’s mastership, integrating, government, union, and teachers was considered a democratic progress, its final result of the work of this group was a draft, in many features, far from national guidance for the career path elaboration, especially, concerning to work journey, and the remuneration composition based on bonus policy. The final law, approved after the adjustment process afterward the public workers strike in 2010, promoted the teacher’s career appreciation in the county, ensuring the professional development by the conjunction of degrees, employment period, quinquennium, sixth part, and other benefits conquered by the professional category.